Effect of Giving MMS (Multiple Micronutrient Supplement) Tablets on Changes in Anemia Status in Pregnant Women: A Quasi-Experimental Study - Katili, Dwi Nur Octaviani (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
Anemia in pregnancy is a health problem which impacts the mother and fetus, includes the risk of bleeding, premature birth, and low birth weight. One effort to overcome this condition is through giving nutritional supplement. This study aims to evaluate the effectiveness of administering Multiple Micronutrient Supplement (MMS) tablets in increasing hemoglobin levels in pregnant women who experience anemia. The research method used a randomized controlled study design such as an experiment with pre-test dan post-test with control group design. Respondents were pregnant women in their third trimester with a diagnosis of mild to moderate anemia, who were given MMS tablets for 30 days. Hemoglobin level data were measured before and after the intervention. The results showed a significant increase in hemoglobin levels after the administration of MMS with p-value(0.01<0.05), indicating that MMS tablets are effective as nutritional therapy to treat anemia in pregnancy. This study confirms that giving MMS supplements can be an alternative strategy in anemia control programs in pregnant women, especially in areas with high anemia incidence.